Food microbiology laboratory for the food science student : a practical approach - Shen, Cangliang; Zhang, Yifan (Springer, 2017)
This book is designed to give students an understanding of the role of microorganisms in food processing and preservation; the relation of microorganisms to food spoilage, foodborne illness, and intoxication; general food processing and quality control; the role of microorganisms in health promotion; and federal food processing regulations. The listed laboratory exercises are aimed to provide a hands-on-opportunity for the student to practice and observe the principles of food microbiology. Students will be able to familiarize themselves with the techniques used to research, regulate, prevent and control the microorganisms in food and understand the function of beneficial microorganism during food manufacturing process.
Includes index.
Keywords: Food -- Microbiology -- Laboratory manuals.; elektronické knihy; electronic books